Socioeconomic position and depression in South African adults with long-term health conditions: a longitudinal study of causal pathways. (14th August 2017) - Elwell-Sutton, T.; Folb, N.; Clark, A.; Fairall, L. R.; Lund, C.; Bachmann, M. O.
Abstract : Aims: There is convincing evidence that lower socioeconomic position is associated with increased risk of mental disorders. However, the mechanisms involved are not well understood. This study aims to elucidate the causal pathways between socioeconomic position and depression symptoms in South African adults. Two possible causal theories are examined: social causation, which suggests that poor socioeconomic conditions cause mental ill health; and social drift, which suggests that those with poor mental health are more likely to drift into poor socioeconomic circumstances. Methods: The study used longitudinal and cross-sectional observational data on 3904 adults, from a randomised trial carried out in 38 primary health care clinics between 2011 and 2012. Structural equation models and counterfactual mediation analyses were used to examine causal pathways in two directions. First, we examined social causation pathways, with language (a proxy for racial or ethnic category) being treated as an exposure, while education, unemployment, income and depression were treated as sequential mediators and outcomes. Second, social drift was explored with depression treated as a potential influence on health-related quality of life, job loss and, finally, income. Results: The results suggest that the effects of language on depression at baseline, and on changes in depression during follow-up, were mediated through education and income but not through unemployment. Adverse effects of unemployment and job loss on depression appeared to be mostly mediated through income. The effect of depression on decreasing income appeared to be mediated by job loss. Conclusions: These results suggest that both social causation and social selection processes operate concurrently. This raises the possibility that people could get trapped in a vicious cycle in which poor socioeconomic conditions lead to depression, which, in turn, can cause further damage to their economic prospects. This study also suggests that modifiable factors such as income, employment and treatable depression are suitable targets for intervention in the short to medium term, while in the longer term reducing inequalities in education will be necessary to address the deeply entrenched inequalities in South Africa.